The brief of the waqf and the ibtida in Arabic grammar and the fiqh and interpretation - Al Amri, Reem Rami (Journal of Islamic Sciences, 2019)
The Waqf and ebtedaa which mean stopping and beginning is one of the legitimate sciences adopted by Muslim scientist, which must be taken and learned as an aspect of learning to recite the Qur'an and read it to stay as God commanded; as the reading of our master Muhammad and the companions of the Companions, may God be pleased with them. The status of this science is great as it enters into the Arrangement and configuration of the Holy Qur'an, so there is no confusion and no overlap of meaning. Hence the great importance of this science and the real urge to learn it. The explanation of the verses on the waqf and its positions has not ceased. The reader stands on what has been completed and understood, and begins with what should be started. This short study of the waqf and ebtedaa has taken place in three main areas that is grammar, interpretation of the Quran and Fiqh. The three were not included in the previous research which was limited to grammar, or interpretation only in most cases. To be a comprehensive research of everything related to this science and to explain all its details.
Keywords: Waqf and ebtedaa; Quran grammar; Al-Sabouni; Fiqh